Analisa Putusan International Center for Settlement of Investment Dispute terhadap Perkara No. ARB/12/14 dan ARB/12/40 dapat meningkatkan Imunitas Negara Indonesia sebagai Host Country - Friska Pasaribu (CV. Syntax Corporation Indonesia, 2022)
The right of immunity is the privilege of a country to protect and to run its function and authority. To maintain its immunity against foreign investors, Indonesia issues Law No. 30/1999 on Arbitrage and Alternative Dispute Resolution. The arbitration board is exerted to able become a fair alternative and to organize all legal aspects and substances which include national and international arbitration. It can be concluded that Indonesia as the host country has immunity. The research uses normative and descriptive analytical method by analyzing the verdicts through library research by gathering primary and secondary data qualitatively. The result of the research shows that Indonesia's immunity is implicitly recognized by International Center for Settlement of Investment Dispute (ICSID) arbitration. It can be seen in the case of dispute in Churchill Mining Plc. and Planet Mining Pty. Ltd. This case is based on the action of the Kutai Timur Regent that revokes the business License of Mining. This state action is categorized as jure imperii that is legitimated since the Indonesian government does not do denial of justice, according to the Tribunal ICSID. This privilege of the Indonesian government proves that it has its own territorial sovereignty so that as a host country it has followed a fair principle in managing mining and foreign investment.